The Effect of Security Perception, Financial Literacy and Content Marketing on Mutual Fund Purchase Decisions on The Bibit Application with Trust As A Mediation - I Gede Wisnu Satria Chandra Putra; Shirleen Alysia Valencia (Universitas Pelita Harapan, 2025)
This study investigates the factors influencing consumer purchasing decisions on the Bibit mutual fund application, specifically examining the roles of perceived security, financial literacy, and content marketing, with trust acting as a mediating variable. Using a quantitative approach, data were collected from 95 respondents and analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results demonstrate that perceived security has a significant positive effect on user trust, whereas financial literacy and content marketing do not significantly influence trust. However, content marketing was found to significantly enhance financial literacy. Furthermore, trust significantly drives mutual fund purchase decisions and successfully mediates the relationship between perceived security and purchase decisions. These findings indicate that while educational content improves literacy, the perception of security is the primary driver of the trust required for users to commit to investment decisions on the platform.